2006
DOI: 10.1007/s00240-006-0057-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel antioxidant agent, astragalosides, prevents shock wave-induced renal oxidative injury in rabbits

Abstract: Extracorporeal shock-wave lithotripsy (ESWL)-induced renal damage can occur as a result of multiple mechanisms, including small vessel injury and free radical formation. Our previous studies have demonstrated that Astragalus membranaceus (AM), a traditional Chinese herb, could significantly alleviate shock wave-induced renal oxidative injury, and its renoprotective effects were superior to those of varapamil, a calcium antagonist, which were considered to be a powerful agent in treating renal damage during ESW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…[4][5][6] Astragaloside IV exhibits various pharmacological properties, such as anti-inflammatory, [7] anti-viral, [8] anti-aging, [9] anti-oxidant, [10] and so on. Cycloastragenol could delay the onset of cellular aging by increasing telomerase activity, [11] up-regulate the immune system by inducing IL-2 release, [12] and enhance the antiviral function of human CD8…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Astragaloside IV exhibits various pharmacological properties, such as anti-inflammatory, [7] anti-viral, [8] anti-aging, [9] anti-oxidant, [10] and so on. Cycloastragenol could delay the onset of cellular aging by increasing telomerase activity, [11] up-regulate the immune system by inducing IL-2 release, [12] and enhance the antiviral function of human CD8…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that herbal formulations containing Radix Astragali and some of its constituents could produce hepatoprotective, 2 antiviral 3 and antioxidative effects. 4 Recently, evidence from various animal and clinical studies has demonstrated that Radix Astragali may possess anticarcinogenic property, 5 which could attenuate the systemic side effects of conventional antineoplatic drugs. 6 Nonsteroidal anti-inflammatory drug (NSAID)-activated gene (NAG-1) is a novel therapeutic target which contributes to the antitumorigenic and proapoptotic effects in various cancer cells.…”
mentioning
confidence: 99%
“…Different conditions in humans (1-3, 9, 13, 14) and experimental animals like rabbits (15), dogs (4, 6, 16), pigs (2, 17) and rats (5, 11) confirm the ESW injury on the renal parenchyma. Some factors can Table 1 produce contradictory results, including the sample size, different equipment with different energy principles, the number of impulses and the focus size (6).…”
Section: Commentsmentioning
confidence: 90%